Perception of Prson Management Personnel of Inmates’ Accessibility and Utilisation of Library Resources Writing Senbior School Certificate Examiantion in Nigeria - Issac Oluwdare Busayo (IJoLIS, 2024)
This study examines the perception of prison management personnel of inmates' accessibility and utilisation of library resouces in writing Senior School Certificate Examination (SSCE) in Nigerial.